From 'Christians doing development' to 'doing Christian development': the changing role of religion in the international work of Tearfund. Issue 2 (17th February 2018) - Freeman, Dena
ABSTRACT: This article seeks to bring more nuance to recent discussions about the role of faith in religious development NGOs. It takes an in-depth look at Tearfund, a leading Evangelical development NGO, and explores the ways in which faith shapes its conceptualisation of development, its programme design, and its implementation strategy. The article traces the process through which Tearfund actively sought to bring faith into the centre of its development work, and argues that grappling with faith in this way can lead religious development NGOs to innovate new approaches to development that are at least somewhat outside of mainstream development thinking.